Cytokines and Soluble HLA-G Levels in the Acute and Recovery Phases of Arbovirus-Infected Brazilian Patients Exhibiting Neurological Complications - Almeida, Renata Santos; Ferreira, Maria Lúcia Brito; Sonon, Paulin; Cordeiro, Marli Tenório; Sadissou, Ibrahim; Diniz, George Tadeu Nunes; Militão-Albuquerque, Maria de Fátima Pessoa; Franca, Rafael Freitas De Oliveira; Donadi, Eduardo Antonio; Lucena-Silva, Norma (Frontiers in Immunology, 2021)
Severe neurological complications following arbovirus infections have been a major concern in seasonal outbreaks, as reported in the Northeast region of Brazil, where the same mosquito transmitted Zika (ZIKV), Dengue (DENV) and Chikungunya (CHIKV) viruses. In this study, we evaluated the levels of 36 soluble markers, including cytokines, chemokines, growth factors, and soluble HLA-G (Luminex and ELISA) in: i) serum and cerebrospinal fluid (CSF), during the acute phase and two years after the infection (recovery phase, only serum), ii) the relationship among all soluble molecules in serum and CSF, and iii) serum of infected patients without neurological complications, during the acute infection. Ten markers (sHLA-G, IL-10, IL-22, IL-8, MIP-1α, MIP-1β, MCP-1, HGF, VEGF, and IL-1RA) exhibited differential levels between the acute and recovery phases, with pronounced increases in MIP-1α (P<0.0001), MCP-1 (P<0.0001), HGF (P= 0.0001), and VEGF (P<0.0001) in the acute phase. Fourteen molecules (IL-1β, IL-2, IL-3, IL-4, IL-5, IL-6, IL-7, IL-9, IL-13, IL-15, IL-17A, IFN-α, TNF, and G-CSF) exhibited distinct levels between arbovirus patients presenting or not neurological complications. IL-8, EGF, IL-6, and MCP-1 levels were increased in CSF, while RANTES and Eotaxin levels were higher in serum. Soluble serum (IL-22, RANTES, Eotaxin) and CSF (IL-8, EGF, IL-3) mediators may discriminate putative risks for neurological complications following arbovirus infections. Neurological complications were associated with the presence of a predominant inflammatory profile, whereas in non-complicated patients an anti-inflammatory profile may predominate. Mediators associated with neuroregeneration (EGF and IL-3) may be induced in response to neurological damage. Broad spectrum immune checkpoint molecules (sHLA-G) interact with cytokines, chemokines, and growth factors. The identification of soluble markers may be useful to monitor neurological complications and may aid in the development of novel therapies against neuroinflammation.